Franco´s purge of the teaching staff. State of the question . - Grana-Gil, Isabel María; Martin-Zuñiga, Francisco; Sanchidrián-Blanco, María del Carmen (My University, 2014)
One of the most effective tools used by the Franco regimen to control memory and history was the professional purge. This was applied to all civil servants in order to ensure their adherence to the regimen. Totalitarian regimes have always exercised strict control over teachers to ensure its own preservation. As in all dictatorships, teachers have to help consolidate the new structures and maintain the order imposed; for this purpose, teachers are required to reproduce the new ideology, and they are forbidden to diffuse any idea that might delegitimize the regime. In addition, one of the first tasks undertaken by totalitarian governments that get into power after a war or a coup is to control memory and history. Fortunately, nowadays it has been managed to break the wall of silence that the Franco regime raised to hide facts and repressive activities that almost everybody knew, but no one dared talk about it. In this context, one of the issues raised for the last two decades is the teacher purge. When we talk about teacher purge, we tend to think only in suspect ones. No. All teachers were suspect, so they were all subjected to this process. The people who sign this paper, we have extensive experience in the investigation of this historical fact. Each one of us has been the principal investigator, between 2002 and 2008, of an R & D project focused on the impact of this repressive action in the specific case of middle school teachers: high school and regular schools financed by the Ministry of Education. For all these reasons, we think we are able to set as an objective the approximation to one overall assessment of the impact of this depuration in the different teaching levels of the educational system: from our own scientific production, we have a fairly clear understanding of what happened with the teachers of the high schools and regular schools; there are also quite comprehensive studies of the situation in a university environment, and the same happens in the case of primary teachers, although In this case we do not know yet the reality of many of the 52,000 teachers who were purged.
Keywords: Profesores - Historia - España - 1939-1975; Educación; Franquismo; Depuración